PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN GURU DALAM MENGELOLA KELAS DAN PEMANFAATAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR EKONOMI - Nurul Aini; Yon Rizal; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2013)
Education in Indonesia nowadays is faced with the problem of lowlearning outcomes or achievements of learners. It is not independent of the various factors that affect the learning process in the classroom, such as the student’s perceptions of teacher’s skills in classroom management and the utilization ofinstructional media. This study aims to determine whether there is an influence of the student’s perceptions about teacher’s skills in classroom management and the utilization of instructional media towards economic learning outcomes of grade XI Social,SMA N 1 Purbolinggo District East Lampung academic year 2012/2013, amounting to 101 students with a sample size of 81 students. Method used in this research is descriptive verification with Ex Post Facto and Survey approach. Data obtained through documentation, interviews, observation and questionnaires. Hypotheses one and hypotheses two were using simple linearregression, to test the third hypotheses, using multiple linear regression. Based on data analysis results, showing that. 1) There is the influence of student’s perceptions about teacher’s skills in classroom management towards economic learning outcomes of XI Social, SMA N 1 Purbolinggo District East Lampung academic year 2012/2013 as evidenced from the results of the t test calculations show that tcountttable or 7094 1.99. 2) There is the influence of the use of instructional media towards economic learning outcomes of XI Social, SMA Negeri 1 Purbolinggo District East Lampung academic year 2012/2013 asevidenced from the results of the t test calculations show that tcountttable or 4239 1.9. 3) There is the influence of student’s perceptions about teacher’s skills in classroom management and utilization of instructional media towards economic learning outcomes of class XI Social, SMA Negeri 1 Purbolinggo District East Lampung academic year 2012/2013 as evidenced from the results of the test calculations show that Fcount F table or 40,310 3.11.Key words: teacher’s skills in classroom management, the utilization of instructional media.